Synthesis, characterization and photocatalytic activities of modified chalcogenides - Kaba, İbrahim (My University, 2024)
Hydrogen is a promising energy source for addressing environmental issues and photocatalytic hydrogen production from water is a promising renewable energy process. Cadmium sulfide (CdS) is a widely used photocatalyst; however, the photocorrosion problem causing the low stability and fast charge recombination problem causing the low photocatalytic activity are also well-known. To prevent the stability problem, CdxZn1-xS which has tunable optical properties has become forward. MoS2 is used as an additive to semiconductor photocatalysts due to its wide contact interface, inhibition of charge recombination, low cost, high reactivity for H2 evoluation reaction, and enhancement of visible light response. Transition metal carbides such as Mo2C are excellent electrocatalysts for the production of H2; additionally, they serve as good co-catalysts for most photocatalysts. Modified CdXZn1-XS photocatalysts were examined in hydrogen production under solar illumination. In the first part of the study, CdXZn1-XS was prepared using 1,3-diaminopropane (DAP) and then MoS2 added; in the second part of the study Cd0.7Zn0.3S nanorod was prepared using ethylenediamine (EDA)/ water and then MoS2 and MoC-Mo2C were added. Catalysts were characterized by XRD, TEM, SEM, UV-Vis DRS, and electrochemical applications. For the first part, a full factor design was carried out via Minitab 19 to investigate the factors affecting the produced hydrogen amount. Cd/ Zn ratio, MoS2 content, and photocatalyst loading were studied. Photocatalytic hydrogen production results were analyzed by ANOVA (Analysis of Variance) and it was concluded that for maximum hydrogen production, Cd/ Zn ratio should be in the range of 0.5/ 0.5 and 0.7/ 0.3; MoS2 content should be in the range of 2-4% and photocatalyst loading should be 10 mg. For the second part, Cd0.7Zn0.3S nanorods were modified with various amounts of MoS2 and MoC-MoC2. N-Cd0.7Zn0.3S/ 1% MoS2/ 1.0% MoC-Mo2C catalyst showed the best result with 133.5 mmol H2 g-1 h-1, while the hydrogen production rate of N-Cd0.7Zn0.3S was 37.2 mmol g-1 h-1.

Hidrojen, çevresel sorunları çözecek, umut vadeden bir enerji kaynağıdır ve sudan fotokatalitik hidrojen üretimi umut vadeden bir yenilenebilir enerji sürecidir. Kadmiyum sülfür (CdS) yaygın olarak kullanılan bir fotokatalizördür; ancak, düşük kararlılığa neden olan fotokorozyon sorunu ve düşük fotokatalitik aktiviteye neden olan hızlı yük rekombinasyonu sorunu da iyi bilinmektedir. Kararlılık sorununu önlemek için, ayarlanabilir optik özelliklere sahip CdxZn1-xS öne çıkmıştır. MoS2, geniş temas yüzeyi, yük rekombinasyonunu engellemesi, düşük maliyeti, H2 oluşumu reaksiyonu için yüksek reaktivitesi ve görünür ışık tepkisinin iyileştirilmesi nedeniyle yarı iletken fotokatalizörlere katkı maddesi olarak kullanılır. Mo2C gibi geçiş metali karbürleri, H2 üretimi için mükemmel elektrokatalizörlerdir; ayrıca, çoğu fotokatalizör için iyi yardımcı katalizörler olarak hizmet ederler. Modifiye edilmiş CdXZn1-XS fotokatalizörleri solar ışık altında hidrojen üretiminde incelenmiştir. Çalışmanın ilk bölümünde, CdXZn1-XS, 1,3-diaminopropan (DAP) kullanılarak hazırlanmış ve ardından MoS2 eklenmiştir; çalışmanın ikinci bölümünde, Cd0.7Zn0.3S nanoçubuklar, etilendiamin (EDA)/ su kullanılarak hazırlanmış ve ardından MoS2 ve MoC-Mo2C eklenmiştir. Katalizörler XRD, TEM, SEM, UV-Vis DRS ve elektrokimyasal uygulamalarla karakterize edilmiştir. İlk bölümde, üretilen hidrojen miktarını etkileyen faktörleri araştırmak için Minitab 19 aracılığıyla tam faktör tasarımı gerçekleştirilmiştir. Cd/ Zn oranı, MoS2 içeriği ve fotokatalizör yüklemesi incelenmiştir. Fotokatalitik hidrojen üretim sonuçları ANOVA (Varyans Analizi) ile analiz edilmiştir ve maksimum hidrojen üretimi için Cd/ Zn oranının 0.5/ 0.5 ile 0.7/ 0.3 aralığında; MoS2 içeriğinin %2-4 aralığında ve fotokatalizör miktarının 10 mg olması sonucuna varılmıştır. İkinci kısım için, Cd0.7Zn0.3S nanoçubuklar çeşitli miktarlarda MoS2 ve MoC-Mo2C ile modifiye edilmiştir. N-Cd0.7Zn0.3S/ 1% MoS2/ 1.0% MoC-Mo2C katalizörü 133.5 mmol H2 g-1 h-1 ile en iyi sonucu gösterirken, N-Cd0.7Zn0.3S'nin hidrojen üretim hızı 37.2 mmol g-1 h-1'dir.
Modifiye kalkojenitlerin sentezi, karakterizasyonu ve fotokalitik aktiviteleri
Keywords: Electrochemistry; Elektrokimya Energy; Enerji; Fotokataliz; Hidrojen; Hidrojen üretimi; Hidrojen, Yakıt olarak; Hydrogen; Hydrogen as fuel; Hydrogen production; Photocatalysis; Su ayrıştırma; Water splitting